A SYSTEMATIC LITERATURE REVIEW ON: DIFFUSION OF INNOVATION THEORY (2020–2024) - Azzahra Nabila Syaki; Sambas Ade Kesuma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to conduct a Systematic Literature Review (SLR) on the application and development of the Diffusion of Innovation (DOI) Theory across various research contexts between 2020 and 2024. The theory, introduced by Everett M. Rogers, is typically used to explain how innovations are adopted, spread, and sustained in social systems. However, with the rapid development of digital transformation, artificial intelligence, and new technologies, there is a need to reassess how this theory has been applied and developed in recent years. This study uses the PRISMA method, following the stages of identifying, screening, and analyzing articles from databases such as Scopus and Google Scholar. A total of 20 relevant articles were reviewed and categorized based on the research field, methods used, and key findings. The results show that the DOI theory remains relevant in various fields, such as information technology, healthcare, education, digital finance, and the public sector. The development of the theory has shifted its focus from technological characteristics and users' rational decisions, towards psychological, social, organizational, and environmental factors. Several factors such as trust, perceived security, management support, organizational readiness, and user experience have been shown to be key determinants of successful innovation adoption. These findings indicate that DOI theory has now evolved into a more human-focused, flexible, and context-appropriate model, thus being able to explain the innovation adoption process amidst the digital era, the pandemic, and increasingly rapid technological advances.